Calcium concentration in hypoxic–ischemic encephalopathy during hypothermia. Issue 1 (14th January 2015) - Yamamoto, Yutaka; Ibara, Satoshi; Tokuhisa, Takuya; Hirakawa, Eiji; Yoneda, Satoshi; Kobayashi, Kosuke; Kato, Eiji; Maruyama, Yuko; Maede, Yoshinobu; Kuwabara, Takako
Abstract: Background: The aim of this study was to investigate the relationship between prognosis and the changes in serum‐ionized calcium concentration in neonates with hypoxic–ischemic encephalopathy (HIE) before and during brain hypothermia (BHT). Methods: Serum samples were obtained from 16 HIE neonates who underwent BHT. All patients underwent developmental testing at 18 months of age. Results: Mean serum‐ionized calcium concentration in the poor outcome group (developmental quotient [DQ], <80; nine infants) was significantly lower than in the good outcome group (DQ >80; seven infants), both immediately before and after 6 h of BHT. Mean serum‐ionized calcium concentration significantly decreased in both groups for 6 h, and the lowest adjusted serum‐ionized calcium during 6 h of BHT was <1.05 mmol/L, known as the cut‐off value for poor outcome, in 57.1% of the good outcome group. Conclusion: The influx of calcium into cells continues regardless of neurological prognosis during the early phase of BHT, but BHT might protect some high‐risk patients against neurological damage at low adjusted serum‐ionized calcium concentration.